2007
DOI: 10.1002/chem.200601759
|View full text |Cite
|
Sign up to set email alerts
|

Unmasking Melon by a Complementary Approach Employing Electron Diffraction, Solid‐State NMR Spectroscopy, and Theoretical Calculations—Structural Characterization of a Carbon Nitride Polymer

Abstract: Poly(aminoimino)heptazine, otherwise known as Liebig's melon, whose composition and structure has been subject to multitudinous speculations, was synthesized from melamine at 630 degrees C under the pressure of ammonia. Electron diffraction, solid-state NMR spectroscopy, and theoretical calculations revealed that the nanocrystalline material exhibits domains well-ordered in two dimensions, thereby allowing the structure solution in projection by electron diffraction. Melon ([C(6)N(7)(NH(2))(NH)](n), plane grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

59
833
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 830 publications
(893 citation statements)
references
References 90 publications
(63 reference statements)
59
833
0
1
Order By: Relevance
“…3,8 Since most synthetic routes invoke the pyrolysis of molecular precursors, [9][10][11][12] moreover, the incorporation of additional hetero atoms or hydrogen can hardly be prevented. This was demonstrated recently by Thomas et al who reported on the synthesis of a microcrystalline, largely hydrogen free graphitic carbon nitride-type material by ionothermal treatment of dicyandiamide.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…3,8 Since most synthetic routes invoke the pyrolysis of molecular precursors, [9][10][11][12] moreover, the incorporation of additional hetero atoms or hydrogen can hardly be prevented. This was demonstrated recently by Thomas et al who reported on the synthesis of a microcrystalline, largely hydrogen free graphitic carbon nitride-type material by ionothermal treatment of dicyandiamide.…”
Section: Introductionmentioning
confidence: 99%
“…X-ray powder patterns usually indicate a pronounced stacking disorder of neighboring layers with an interlayer distance amounting to about 3.2 Å . 4,9,13,23,42 Besides X-ray diffraction techniques, 15,[27][28][29][30][31]34,40,[42][43][44] infrared (IR) and Raman spectroscopy 15,20,27,28,32,33,40,45 as well as X-ray photoelectron spectroscopy (XPS) 16,19,26,29,30 are the most commonly employed characterization techniques. As these mostly probe the local environment rather than intermediate or long range properties, no information about the stacking disorder of melon-type materials have been obtained.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations